Sociological Review of Factors Causing the Increase of Street Children in Makassar City - Pratama, Galank; Arsyad, Armin; Kambo, Gustiana A (Global Writing Academica Researching & Publishing, 2024)
Cities that are considered promising by rural communities to seek a better welfare life force them to look for space to fulfill their needs. Public places then become an alternative for them in making a living such as in shopping places, flyovers, and at road intersections. Makassar as one of the metropolitan cities is also inseparable from economic problems and social problems such as the existence of street children. This research was conducted using an in-depth interview method conducted to informants who the author considers capable of providing data and information related to the causes of the increase in the number of street children in Makassar city. The theory used is the theory of space production. The increase in the number of street children in Makassar City is caused by three factors, namely urban development factors. the second factor is urbanization carried out by rural communities to obtain a more decent life, and the third factor is the exploitation behavior carried out by individuals and families of these street children.